2016
DOI: 10.1002/art.39745
|View full text |Cite
|
Sign up to set email alerts
|

Review: Neutrophils as Invigorated Targets in Rheumatic Diseases

Abstract: OLFM4 5 olfactomedin 4; ANCA 5 antineutrophil cytoplasmic antibody; ROS 5 reactive oxygen species; SLE 5 systemic lupus erythematosus; NETs 5 neutrophil extracellular traps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 91 publications
(119 reference statements)
0
24
0
Order By: Relevance
“…Standards of levamisole (Sigma-Aldrich), 13 C 6 -D-levamisole (AlsaChim), D 3 -cocaine (Sigma-Aldrich), and 250 μg/ml certified reference material Cocaine Multi-Component Cocaine Mixture (Sigma-Aldrich, C-088-1ML) were obtained. The drugs and metabolites were extracted from urine by vortexing a 25-μl aliquot of urine and 475 μl water with 0.1% formic acid containing 13 C 6 -D-levamisole and D 3 -cocaine internal standards for 5 minutes.…”
Section: Endothelial Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Standards of levamisole (Sigma-Aldrich), 13 C 6 -D-levamisole (AlsaChim), D 3 -cocaine (Sigma-Aldrich), and 250 μg/ml certified reference material Cocaine Multi-Component Cocaine Mixture (Sigma-Aldrich, C-088-1ML) were obtained. The drugs and metabolites were extracted from urine by vortexing a 25-μl aliquot of urine and 475 μl water with 0.1% formic acid containing 13 C 6 -D-levamisole and D 3 -cocaine internal standards for 5 minutes.…”
Section: Endothelial Cytotoxicity Assaymentioning
confidence: 99%
“…Most of the prior investigations into the mechanisms of drug-induced autoimmunity have focused upon the effects of these medications on mononuclear cells. The potential contributions of neutrophils to drug-induced autoimmunity have not been extensively studied, yet neutrophil dysregulation plays an increasingly recognized role in the pathogenesis of certain autoimmune diseases including AAV and SLE (13).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence indicating that neutrophils have an active role in the pathogenesis of RA . Inflammatory joint effusions of RA patients are characterized by a high number of neutrophils in the SF where these cells mediate tissue destruction after improper activation . The aim of the present study was to analyze the characteristics of neutrophils infiltrating the inflamed joints in the presence of ACPA autoantibodies in SF of RA patients.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the generation of proteins modified by citrullination in the joint by activation of PADs is a key stage to trigger anticitrulline immunity in ACPA-positive patients [31]. Thus, NET formation is likely to play a pathogenic role in RA as NETosis may serve as an important source of citrullinated autoantigens [4]. Although this study involved a relatively low number of SF samples, we observed that in vitro incubation of neutrophils with ACPA high SF resulted in an increase of ROS production in PMA-primed cells, and also in extracellular DNA release.…”
Section: Discussionmentioning
confidence: 99%
“…These structures in turn are bound by autoantibodies, commonly found in the blood of SLE patients, and this leads to their uptake by plasmacytoid dendritic cells and stimulation of interferon production. This vicious cycle of interferon-driven neutrophil activation is proposed to be a potential target of therapeutic intervention in SLE [23]. …”
Section: Neutrophil Heterogeneity – Not All Neutrophils Are Equalmentioning
confidence: 99%